Application of Delayed Phase Contrast-enhanced Chest Computed Tomography in the Evaluation of Solid Solitary Pulmonary Nodules at the National Lung Hospital - Van Luong, Hoang; Quy Loi, Dang (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2025)
Abstract: Objective: To evaluate the diagnostic value of delayed-phase contrast-enhanced chest computed tomography (CT) at 60 seconds after contrast injection in differentiating benign from malignant solid solitary pulmonary nodules (SPNs). Subjects and Methods: A cross-sectional study with both prospective and retrospective components was conducted on 53 patients presenting with solid SPNs detected on delayed-phase contrast-enhanced chest CT. The attenuation values (Hounsfield Units – HU) of the lesions were measured before and 60 seconds after contrast administration. The enhancement degree (ΔHU) was analyzed to distinguish between benign and malignant nodules. Histopathological results served as the diagnostic gold standard. Results: The proportion of malignant nodules was high, accounting for 79.2%. Malignant lesions were predominantly peripheral (71.4%), had spiculated or irregular margins (75.7%), and frequently exhibited pleural tags (50%). The mean nodule size was 17.1 ± 5.1 mm, with most nodules measuring 15–30 mm being malignant. Malignant nodules showed significantly higher post-contrast attenuation values than benign ones (85.9 ± 21.1 vs. 67.6 ± 14.8 HU; p = 0.01). The mean enhancement (ΔHU) in malignant nodules was 33.5 ± 16.0 HU-over three times greater than that of benign lesions (10.8 ± 7.0 HU; p < 0.001). Using a ΔHU threshold of ≥15 HU, delayed-phase CT achieved a sensitivity of 95.2%, specificity of 72.7%, and overall accuracy of 90.5%, demonstrating high diagnostic performance in differentiating benign from malignant SPNs. Conclusion: Delayed-phase contrast-enhanced chest CT is an effective quantitative imaging tool for differentiating benign and malignant solid solitary pulmonary nodules. However, integration with additional clinical, imaging, and histopathological parameters is recommended to further improve diagnostic accuracy. Keywords: Solitary lung nodules, lung cancer.